SGLT2 inhibitor administration to two patients with diabetes mellitus with ascites due to cirrhosis - Koji Nagayama; Risako Harada; Hiroshi Ajima; Sakurako Orikasa; Misaki Aoshima; Yutaka Oki (Endocrinology, Diabetes & Metabolism Case Reports, 2025)
We used the sodium-glucose cotransporter 2 inhibitor, luseogliflozin in two patients with diabetes mellitus with Child–Pugh classification B cirrhosis and cirrhotic ascites. In each case, luseogliflozin was safely used for over three years and was also considered effective in reducing ascites. In one of the patients in particular, when luseogliflozin was discontinued and switched to insulin treatment before colorectal cancer surgery, ascites accumulation was observed within two weeks, which subsequently decreased rapidly when luseogliflozin was restarted. In this case, the effect of luseogliflozin on ascites was evident by the clear increase and decrease in ascites over a short period of time, as evaluated using body weight, abdominal circumference and CT scan, without changing her other diuretic medication. Although sodium-glucose cotransporter 2 inhibitors need to be used with caution, they might be an option for the treatment of diabetes in patients with cirrhosis.